A new aetosaur genus (Archosauria: Pseudosuchia) from the early Late Triassic of southern Brazil - Desojo, Julia B.; Ezcurra, Martín D.; Kischlat, Edio E. (Zootaxa, 2012)
We describe the new aetosaur Aetobarbakinoides brasiliensis gen. et sp. nov. from the early Late Triassic (late Carnian-early Norian) Brazilian Santa Maria Formation. The holotype is composed of a partial postcranium including several cer-vical and dorsal vertebrae and ribs, one anterior caudal vertebra, right scapula, right humerus, right tibia, partial right pes,and anterior and mid-dorsal paramedian osteoderms. Aetobarbakinoides is differentiated from other aetosaurs by the pres-ence of cervical vertebrae with widely laterally extended prezygapophyses, mid-cervical vertebrae with anterior articularfacet width more than 1.2 times wider than the posterior one, anterior caudal vertebrae with extremely anteroposteriorlyshort prezygapophyses, elongated humerus and tibia in relation to the axial skeleton, and paramedian osteoderms with aweakly raised anterior bar. A cladistic analysis recovered the new species as more derived than the South American generaAetosauroides (late Carnian-early Norian) and Neoaetosauroides (late Norian-Rhaetian), and it is nested as the sister-tax-on of an unnamed clade, composed of Typothoracisinae and Desmatosuchinae, due to the absence of a ventral keel in thecervical vertebrae. Aetobarbakinoides presents a skeletal anatomy previously unknown among South American aetosaurs,with the combination of presacral vertebrae with hyposphene, anteroposteriorly short and unkeeled cervical vertebrae,gracile limbs, and paramedian osteoderms with a weakly raised anterior bar. Aetobarbakinoides is among the oldest knownaetosaurs together with Aetosauroides from Argentina and Brazil and Stagonolepis robertsoni from Scotland, indicatinga widely distributed early record for the group. In addition, the recognition of a suite of derived features in Aetobarbaki-noides, which is one of the oldest known aetosaurs, is in agreement with an older origin for the group, as it is expected by the extensive ghost lineages at the base of the main pseudosuchian clades.